The Aerodynamics of Heavy Vehicles III Trucks, Buses and Trains - Dillmann, Andreas; Orellano, Alexander; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume contains papers presented at the International conference "The Aerodynamics of Heavy Vehicles III: Trucks, Buses and Trains" held in Potsdam, Germany, September 12-17, 2010 by Engineering Conferences International (ECI). Leading scientists and engineers from industry, universities and research laboratories, including truck and high-speed train manufacturers and operators were brought together to discuss computer simulation and experimental techniques to be applied for the design of more efficient trucks, buses and high-speed trains in the future.   This conference was the third in the series after Monterey-Pacific Groove in 2002 and Lake Tahoe in 2007.  The presentations address different aspects of train aerodynamics (cross wind effects, underbody flow, tunnel aerodynamics and aeroacoustics, experimental techniques), truck aerodynamics (drag reduction, flow control, experimental and computational techniques) as well as computational fluid dynamics and bluff body, wake and jet flows.
Train Aerodynamics -- Train Aerodynamics - Cross-wind Effects -- Train Aerodynamics - Experimental Techniques -- Train Acoustics -- Truck Aerodynamics -- Truck Aerodynamics - Drag Reduction -- Truck Aerodynamics - Experimental Techniques -- Truck Aerodynamics - Computations -- Truck Aerodynamics - Active Flow Control -- Bluff Body, Wake and Jet Flows.
Keywords: Fluid mechanics; Automotive engineering; Transportation engineering; Traffic engineering; Engineering Fluid Dynamics; Automotive Engineering; Transportation Technology and Traffic Engineering